Kinetic analysis of MgB2 layer formation in advanced internal magnesium infiltration (AIMI) processed MgB2 wires. (1st September 2015) - Li, G.Z.; Sumption, M.D.; Collings, E.W.
Abstract: Significantly enhanced critical current density ( J c ) for MgB2 superconducting wires can be obtained following the advanced internal Mg infiltration (AIMI) route. But unless suitable precautions are taken, the AIMI-processed MgB2 wires will exhibit incomplete MgB2 layer formation, i.e. reduced superconductor core size and hence suppressed current-carrying capability. Microstructural characterization of AIMI MgB2 wires before and after the heat treatment reveals that the reaction mechanism changes from a "Mg infiltration-reaction" at the beginning of the heat treatment to a "Mg diffusion-reaction" once a dense MgB2 layer is formed. A drastic drop in the Mg transport rate from infiltration to diffusion causes the termination of the MgB2 core growth. To quantify this process, a two-stage kinetic model is built to describe the MgB2 layer formation and growth. The derived kinetic model and the associated experimental observations indicate that fully reacted AIMI-processed MgB2 wires can be achieved following the optimization of B particle size, B powder packing density, MgB2 reaction activation energy and its response to the additions of dopants.